2020
DOI: 10.1007/s10072-020-04932-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19, de novo seizures, and epilepsy: a systematic review

Abstract: Objective We discuss the evidence on the occurrence of de novo seizures in patients with COVID-19, the consequences of this catastrophic disease in people with epilepsy (PWE), and the electroencephalographic (EEG) findings in patients with COVID-19. Methods This systematic review was prepared according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. MEDLINE, Scopus, and Embase from inception to August 15, 2020 were systematically searched. These key w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 84 publications
(136 reference statements)
1
74
0
1
Order By: Relevance
“…The ratio of confirmed cases of COVID-19 among the participants of our survey (eight cases in a sample of 111, or 7.2%) was similar to the one in the general population in Lithuania towards the end of the study (147,984 of confirmed cases in a population of 2,794,090 inhabitants, or 5.3%) [ 9 ]. However, COVID-19-related results (e.g., seizure exacerbation in one of the patients) are limited by a small sample size and the non-inclusion of severe or lethal COVID-19 cases, for which data are yet scant in the literature as well [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of confirmed cases of COVID-19 among the participants of our survey (eight cases in a sample of 111, or 7.2%) was similar to the one in the general population in Lithuania towards the end of the study (147,984 of confirmed cases in a population of 2,794,090 inhabitants, or 5.3%) [ 9 ]. However, COVID-19-related results (e.g., seizure exacerbation in one of the patients) are limited by a small sample size and the non-inclusion of severe or lethal COVID-19 cases, for which data are yet scant in the literature as well [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A deterioration of their physical and psychological condition was mostly associated with a lack of timely medical services, disrupted use or supply of antiseizure drugs (ASDs) and the consequences of strict lockdown measures, which induced mental health problems and were associated with seizure exacerbation [ 1 , 2 , 3 , 4 , 5 ]. While there is currently only limited evidence that COVID-19 is more severe or lethal in those with comorbid epilepsy, the spread of COVID-19 still exposes patients to a substantial risk of severe respiratory complications and often results in lockdowns, which disturb access to healthcare [ 6 , 7 , 8 ]. There were two periods of lockdown in Lithuania in 2020 (March–June and November–December) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with COVID-19, de novo seizures were reported. 13 Electroencephalography (EEG) findings of patients with SARS-CoV-2 infection showed sporadic epileptiform activity (mostly frontal sharp waves) and generalized background slowing, particularly in patients with a decreased level of consciousness. 14 No abnormalities during the EEG recording were found.…”
Section: Discussionmentioning
confidence: 99%
“…with seizures (even in people without pre-existing epilepsy) in many previous studies. 12 Furthermore, this pandemic has caused significant disruption in the quality and availability of care to PWE, as well as increased stress and social isolation rates; these may contribute to exacerbation or breakthrough seizures in PWE. 11,13 Finally, some patients with COVID-19 may develop a seizure as a consequence of hypoxemia, organ failure, metabolic derangements, or drug-drug interactions.…”
Section: Patients With Epilepsy May Have Different Clinical Manifestamentioning
confidence: 99%